Clinicopathological characteristics and loss of mismatch repair protein expression in Chinese upper tract urothelial carcinomas - Shang, Zhi; Jin, Shengming; Wang, Wenwen; Wei, Yu; Gu, Chengyuan; Yang, Chen; Zhu, Yu; Zhu, Yao; Shen, Yijun; Wu, Junlong; Ye, Dingwei (Frontiers in Oncology, 2022)
Expression of DNA mismatch repair Protein (MLH1, PMS2, MSH2 and MSH6) in Upper Tract Urothelial Carcinoma (UTUC) has been explored in western cohorts, but it is rarely reported in eastern cohorts. We aimed to assess the loss of mismatch repair (MMR) protein expression among Chinese UTUC patients and study its clinicopathological implications. We enrolled 175 UTUC patients at our center and tested the expression of MMR proteins by immunohistochemistry. Then we explored these patients’ clinicopathological characteristics. We found loss of MMR proteins in 19 (10.9%) of 175 patients in our cohort (6 MSH2 and MSH6; 2 MSH6 alone; 6 MSH2 alone; 3 MLH1 and PMS2; 2 PMS2 alone). Loss of MMR proteins were not significant prognostic factors of relapse-free survival for these patients. In addition, patients with lower T stage or with bladder cancer history were more likely to have the loss of MMR protein expression. At last, two metastatic patients (MSH2&MSH6 loss; MSH2 loss) with loss of MMR protein experienced tumor recession after several cycles of anti-PD-1 immunotherapy. In conclusion, this is the largest Chinese UTUC cohort study to date that explores the loss of MMR protein expression. The rate of MMR loss observed was comparable to that in the western UTUC cohort, supporting universal UTUC screening in China. Furthermore, a subset of advanced UTUCs with MMR protein loss are probably immunogenic, for whom single or combined immunotherapy may be potential therapeutic options in the future.